SOIL PROPERTIES AND CARBON ACUMULATION IN AN INTEGRATED CROP-LIVESTOCK SYSTEM UNDER NO-TILLAGE - Costa, Nidia Raquel [UNESP]; Andreotti, Marcelo [UNESP]; Mascarenhas Lopes, Keny Samejima [UNESP]; Yokobatake, Kazuo Leonardo [UNESP]; Ferreira, Joao Paulo [UNESP]; Pariz, Cristiano Magalhaes [UNESP]; Batista Bonini, Carolina dos Santos [UNESP]; Longhini, Vanessa Zirondi [UNESP] (Soc Brasileira De Ciencia Do Solo, 2015)
In production systems such as the integrated crop-livestock system (ICL) under no-tillage, improvements have been observed in chemical, physical, and biological soil properties. Therefore, we aimed to evaluate the changes in chemical and physical soil properties, as well as carbon (C) accumulation, in an Oxisol under irrigated conditions in the Cerrado (Brazilian tropical savanna) in an ICL system under no-tillage. The experiment was carried during the growing of 2010/2011, 2011/2012, and 2012/2013. A randomized block experimental design with four replications was used. Treatments were arranged in split plots in time, and the experimental plots were composed of the following: maize and forage sorghum grown separately or intercropped with the forages Urochloa brizantha var. Xaraes and Megathyrsus maximum var. Tanzania for ensiling; forage species in the between-harvest period; and the soybean crop in succession. In addition to the initial characterization, five evaluations (seasons) of the soil chemical and physical properties at the end of each production cycle were performed while carrying out the experiment. Production in the ICL system under no-tillage, even with high nutrient export and machine traffic, were efficient in maintaining and even improving soil fertility and soil C stocks. Over a three-year period, the ICL led to reduction in soil compaction through the positive effect of increased macroporosity and total porosity and decreased resistance to penetration and bulk density, in the 0-0.10 and 0.10-0.20 m soil layers.
Keywords: organic matter; cation exchange capacity; resistance to penetration; bulk density; soil carbon stock